Rozwój doliny dolnej Łupawy w późnym plejstocenie - Czerniawska, Jolanta (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2007)
The lower £upawa valley is situated in the Gardno Phase marginal zone. The Gardno Phase represents a short ice readvance on the North Polish Plain. According to ROTNICKI (2001) Gardno Phase should be situated between 14 700 and 14 500 years B.P. The fossil ice-dammed lake has been discovered in the lower £upawa valley. Based on the analysis of the materials the extent of ice-dammed lake has been determined. Its dimensions are: width – 1,2 km, length – 5 km. During the first ice recession phase the ice-dammed lake disappeared. The first ice recession phase is situated between 14 300 and 14 000 years B.P. (ROTNICKI 2001). After that the aggradation of the alluvial fan of the £upawa began. Fossil channels of braided £upawa can be found in its top part. The oldest organogenic infillings of these channels started to accumulate 13 800± 270 years B.P. (ROTNICKI & BORÓWKA 1995). According to ROTNICKI & BORÓWKA (1995) one of the youngest organogenic infillings of these channels started to accumulate 6 700±70 years B.P.